Calidad de la Energía de un Autogenerador Fotovoltaico a Pequeña Escala Conectado a la Red: Caso de Estudio - Luis David Pabón-Fernández; Oscar Javier Suarez Sierra; Luis Felipe González Archila (Mundo Fesc)
This article presents a power quality study conducted on a small-scale solar photovoltaic self-generator located in the Andean region of Colombia, specifically in the municipality of Pamplona, ​​Norte de Santander. The study was performed using a properly calibrated Fluke 434-II power analyzer, which allowed data to be obtained at the common coupling point between the building's existing electrical installation and the photovoltaic generator. In this way, the power quality analysis is performed following international standards such as IEEE 1159 and IEEE 519. Similarly, active and reactive energy consumption data were analyzed, where 99 events were presented and classified, such as voltage harmonics, overvoltages, sags, among others. Finally, recommendations are made as possible solutions to the electromagnetic phenomena related to power quality and power consumption events found.